Unleashing Gamification's Potential: How Reward, Competition, and Cooperation Drive User Retention in Indonesian Mobile Payments - Rahadian Achmad Prayoga (Open Access Indonesia Journal of Social Sciences, 2025)
The mobile payment sector in Indonesia is experiencing rapid growth, yet platforms face significant challenges in user retention. Gamification, the application of game-like elements in non-game contexts, has emerged as a promising strategy to enhance user engagement and loyalty. This study investigates the impact of gamification on user retention within Indonesian mobile payment applications, utilizing the theoretical lenses of affordance theory and social impact theory. Employing structural equation modeling (SEM) with a partial least squares (PLS) approach, we analyzed data collected from an online survey of 462 fintech application users in Indonesia. The findings reveal that reward, competition, and cooperation affordances exert positive and significant effects on social impact dimensions, specifically compliance, identification, and internalization. However, feedback affordance did not demonstrate a significant effect on these dimensions. Furthermore, narrative affordance, representing the storytelling aspect of gamification, moderates the relationship between gamified artifactual affordances and social impact. Notably, compliance strongly influences user retention, while internalization and identification do not show significant direct effects. This research offers valuable insights for mobile payment platforms seeking to cultivate user retention by strategically designing reward systems, fostering healthy competition, facilitating cooperation among users, and crafting compelling narratives to enhance the gamified experience. This study contributes to the body of knowledge by extending the understanding of gamification affordances and their interplay with narrative affordance within mobile payment platforms, providing a novel perspective on how these elements collectively shape user retention in the Indonesian context through the lens of social impact theory.